1998
DOI: 10.1001/archpsyc.55.11.995
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Cortisol-Induced Increases in Plasma Leptin Concentration in Healthy Humans

Abstract: The results indicate an important role for GCs in the short-term regulation of human leptin secretion. Glucocorticoid-induced increases in leptin secretion suggest a mechanism that may contribute to anorexia and weight loss during stress and disease states such as major depression, if these conditions are associated with sustained increases in plasma leptin concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 65 publications
5
74
1
2
Order By: Relevance
“…In vitro incubation of rat adipocytes with a synthetic GC, dexamethasone, increases leptin mRNA level and release as early as 2 h (8). Our laboratory (58) and others (36,56) find that, in humans, oral GCs increase leptin mRNA and serum leptin levels by approximately twofold, 24 -48 h after administration. Coadministration of a pulse of GCs with a meal or insulin increases serum leptin after 5-7 h, but it is not known whether this is because of an increase in leptin mRNA (34,35).…”
Section: Chronic Changes In Nutritional Status Regulate Leptin At Thementioning
confidence: 69%
“…In vitro incubation of rat adipocytes with a synthetic GC, dexamethasone, increases leptin mRNA level and release as early as 2 h (8). Our laboratory (58) and others (36,56) find that, in humans, oral GCs increase leptin mRNA and serum leptin levels by approximately twofold, 24 -48 h after administration. Coadministration of a pulse of GCs with a meal or insulin increases serum leptin after 5-7 h, but it is not known whether this is because of an increase in leptin mRNA (34,35).…”
Section: Chronic Changes In Nutritional Status Regulate Leptin At Thementioning
confidence: 69%
“…29 Moreover, we have recently shown that a single (nearphysiological) dose of hydrocortisone (40 mg) signi®-cantly increases plasma leptin. 30 In conclusion, the natural glucocorticoid, hydrocortisone, increases leptin mRNA expression in human adipose tissue, and increases plasma leptin levels in healthy subjects. The metabolic signi®cance of the interaction between glucocorticoids and leptin remains to be elucidated.…”
Section: Discussionmentioning
confidence: 87%
“…(Chavez et al, 1997;Warne, 2009) leptin? (Dagogo-Jack et al, 1997;Miell et al, 1996;Newcomer et al, 1998;Slieker et al, 1996;York, 1996) CRH and Ucn 3 (Bernier, 2006;Ohata and Shibasaki, 2011;Smagin et al, 1998) CART (Kask et al, 2000;Xu et al, 2010) Nesfatin-1 (Goebel et al, 2009;Stengel et al, 2011) NPW (Beck et al, 2010) Melanocortins (Liu et al, 2007;Yamano et al, 2004) central monoaminergic systems (Gibson, 2006) autonomous nervous system (Seematter et al, 2004) Stress induces hyperphagia due to reduction of: sensor specific satiety (Ahn and Phillips, 2012;Ortolani et al, 2011) stressor aversiveness (Piazza and Le Moal, 1997) CRH signaling? (Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004) due to activation of central reward pathways (Piazza and Le Moal, 1997), due to alterations in gut microbiota (Tehrani et al, 2012) Glucocorticoids induce hyperphagia (Dallman, 1993;Drapeau et al, 2003;Epel et al, 2000;Tataranni et al, 1996) due to increased signaling of: NPY (Gyengesi et al, 2010;Krysiak et al, 1999;McKibbin et al, 1992;White et al, 1994;Wilding et al, 1993), AgRP (Coll et al, 2005;Savontaus et al, 2002), Nociceptin …”
Section: Q4mentioning
confidence: 99%
“…GCs can interact with leptin in the long-term regulation of energy intake and body adiposity. or leptin receptor deficiency is attenuated by ADX (York, 1996), supraphysiological doses of exogenous GCs increase leptin mRNA levels in ob/ob mice, leptin secretion in cultured rat adipocytes (Slieker et al, 1996), and circulating leptin concentrations in normal and obese humans (Dagogo-Jack et al, 1997;Miell et al, 1996;Newcomer et al, 1998). But these authors did not measure food intake, and it remains unknown whether GC-induced hyperleptinemia is followed by anorexia in humans.…”
Section: Central Anorexigenic Effectmentioning
confidence: 99%